Application of Machine Learning Methods in the Study of Mongolian Cultural Heritage - Perenleillkhundev, Gantuya; Namjil, Bayarsaikhan; Batsuuri, Suvdaa (Studia Folclorica, 2024)
Recently, countries worldwide have widely applied artificial intelligence (AI) methods and technologies to study their arts and culture. In Mongolia, research using machine learning methods has been conducted in oral literature, linguistics, history, and archaeology, focusing on tangible and intangible cultural heritage, and has produced promising results. In this study, we conducted experiments using these methods to research Mongolian traditional culture and literature. Specifically, we selected data sets from Mongolian cultural heritage, including horse stamp marks, petroglyphs, and long song lyrics from oral literature. We introduced the general methodology for creating data sets, detecting and recognizing patterns, and explained the experimental results. Монголын соёлын өвийн судалгаанд машин сургалтын арга ашиглах нь Хураангуй: Өнөө үед дэлхийн улс орнууд өөрийн урлаг, соёлын судалгаанд хиймэл оюуны (artificial intelligence), арга, технологиудыг өргөн ашиглах болсон. Бид энэхүү ажлаар монголын соёл, утга зохиолын судалгаанд дээрх аргуудыг ашигласан. Үүнд монголын соёлын өвөөс адууны тамга, хадны зураг, утга зохиолоос уртын дууны шүлгийн өгөгдлийг сонгон өгөгдлийн багц үүсгэх, дүрс илрүүлэх, таниулахад хэрэглэсэн ерөнхий аргачлалыг танилцуулан, туршилтын үр дүнг тайлбарлав. Түлхүүр үг: Адууны тамга, хадны дүрс, уртын дуу ангилах, танилт, объект илрүүлэх, машин сургалт